Nanocrystalline ZnS dispersed in polymer electrolyte (PEO :NH4I): Preparation and electrical conductivity measurements - Singh P.K.; Pratap R.; Chandra A. (My University, 2025)
Nano-composites of a polymer electrolyte PEO:NH4I (80:20) have been prepared by dispersing nano-size ZnS crystallites in it. The measured band gap of dispersed ZnS is ∼3.9 eV and its particle size as estimated from the XRD linewidths is ∼ 11 nm. Detailed I-V and polarisation studies show that the composite polymer film is a mixed (ionic+electronic) conductor and that the dispersoid ZnS is n-type. The total electrical conductivity Vs composition studies show two peaks at the ZnS concentrations of 4 and 10 wt% which can be qualitatively explained on the basis of two-percolation threshold model.